Towards an accurate and fast computation of discrete Tchebychev moments for binary and grey‐level images. Issue 4 (1st April 2018) - Benrais, Lamine; Baha, Nadia
Abstract : The discrete Tchebychef moments (DTMs) are a set of discrete orthogonal moments applied in the field of objects description and image analysis. They show great precision in providing precise features representation capability for any given image. While using these models seems to be the preferred way for object description, the trade‐off is the considerable calculation time they require. The goal is to explore the feasibility of preparing and using a pre‐calculated data structure for the computation of the DTMs. To make the pre‐calculated data structure possible, the sizing property of the DTMs is used. Experimental results show the equal accuracy of the calculated moments compared with the classic calculation process while realising a significant decrease in calculation time.